2019
DOI: 10.1002/jcop.22170
|View full text |Cite
|
Sign up to set email alerts
|

Tracking methods and retention for a longitudinal sample of alcohol‐ and drug‐involved women on probation and parole

Abstract: Attrition, or the progressive loss of individuals from a sample, poses a major problem in fields that carry out research to inform policy and program design. Attrition This is the author manuscript accepted for publication and undergone full peer review but has not been through the copyediting, typesetting, pagination and proofreading process, which may lead to differences between this version and the Version of Record. Please cite this article as

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…“I was kind of scared [walking alone], and I’m a very strong woman, so that was kind of upsetting to me…” For women using public transit, safety and accessibility of transportation were meaningful barriers in women’s job searches. This finding is consistent with other research that has acknowledged transportation safety as a systematic disadvantage faced by system-involved women (Northcutt Bohmert et al, 2019).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…“I was kind of scared [walking alone], and I’m a very strong woman, so that was kind of upsetting to me…” For women using public transit, safety and accessibility of transportation were meaningful barriers in women’s job searches. This finding is consistent with other research that has acknowledged transportation safety as a systematic disadvantage faced by system-involved women (Northcutt Bohmert et al, 2019).…”
Section: Resultssupporting
confidence: 93%
“…The final sample size used for this research was 60, and statistical analyses showed no significant differences in women who were and were not retained between the first and second interviews. Methods for participant retention were informed by past work with system-involved women on probation and parole (Northcutt Bohmert et al, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…This includes building a trusting environment by pairing participants with the same staff member throughout the study [ 15 ]. Studies also need to build flexible environments in which staff members are familiar with participants’ barriers to continued participation and can accommodate their needs [ 15 , 17 ]. As the time and resources required to participate in on-going study activities may act as a barrier to retention, staff being flexible on the timing of study visits (e.g., evenings, weekends), offering virtual options, and working with participants to address their specific needs (e.g., childcare) is crucial [ 8 , 9 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…As the time and resources required to participate in on-going study activities may act as a barrier to retention, staff being flexible on the timing of study visits (e.g., evenings, weekends), offering virtual options, and working with participants to address their specific needs (e.g., childcare) is crucial [ 8 , 9 , 15 ]. Finally, researchers have found success in retention by increasing the persistence and variety of communications with participants [ 7 , 17 ].…”
Section: Introductionmentioning
confidence: 99%